Importance of Epigraphy in the Study of History and Civilizationتاریخ و تہذیب میں کتبہ شناسی کی اہمیت۔۔۔۔۔۔: The case of Arabic and Persian Inscriptions of Bengal بنگال کے عربی اور فارسی کتبات پر ایک نظر۔۔۔۔۔۔ - پروفیسر ڈاکٹر محمد یوسف صدیق (FIKR-O NAZAR فکر ونظر, 2009)
Inscriptions are a valuable source for understanding human civilization and culture as they serve as a missing link to the past history offering many valuable historical clues which are not easily available otherwise. As Islamic culture attaches special importance to writing, inscriptions became a significant element of Islamic architectural decoration ever since the first century AH. Islamic culture considered inscriptions a powerful medium to convey visual, cultural, and spiritual messages. Inscriptions at times help us in understanding the political, administrative, social, religious and cultural history of a region. Interestingly, epigraphy emerged as an important discipline in Islamic historiographic tradition as early as early ninth/fifteenth century when scholars such as al-Shibi of Makkah started looking at inscriptions with scholarly interest and historical intent.